How Extensible Resources Enhance Service Efficiency in New Retail Enterprises: The Moderating Role of Improvisational Ability - Xu, Bo (Journal of Global Economy, Business and Finance, 2025)
This study addresses the critical challenge of enhancing service efficiency in new retail enterprises. Grounded in the theory of extensible resources, it examines the impact of such resources on the service efficiency of 296 new retail enterprises established in China from 2014 to 2022. The findings demonstrate that extensible resources significantly improve service efficiency, and that this effect is strengthened by the presence of organizational improvisational capability. The research extends the theoretical boundaries of the extensible resources framework and provides practical insights for new retail firms seeking to integrate market, social, intellectual, and technical service resources to optimize their service performance.